Associated factors with anxiety during social isolation by COVID-19 in University Students, Cusco-Peru - Virto-Farfan, Hesed (2023)
Adapting to a different routine has a psychological cost with alterations in response capacity, predisposing people to develop pathologies related to anxiety. Objectives: To determine the association between the factors of the media, psychosomatic, health history, socioeconomic, coping, behaviors towards isolation and anxiety during quarantine by COVID-19 (SARS-COV-2) in university students. Material and Methods: Analytical observational study, using a “Snowball” strategy; 436 responses were collected through an online survey. The instrument used was a questionnaire containing sociodemographic data, epidemiological data referring to the disease (Covid-19) and DASS-21. Anxiety was considered as a dependent variable, and as variables independent the media, health history, socioeconomic status, coping, and finally, isolation behaviors. Results: It consisted of 436 participants, where 58.5% presented anxiety. Conclusions: We found higher levels than the national average prior to the pandemic and higher in comparison to other studies and reviews on anxiety.